Do metacognitions have a moderating role in GAD? An investigation with neuroticism, anxiety sensitivity, and intolerance of uncertainty - Styba-Nelson, Kevin (My University, 2024)
There are many cognitive thought patterns and individual factors that are known to underly the persistent and wide spread worrying of individuals with GAD. This includes the personality trait of neuroticism, as well as the maladaptive cognitions of AS, and IU. Metacognitive beliefs about worry, people’s beliefs about the impact and controllability of worrying, are also known to be a substantial factor in GAD. The present studies sought to investigate this possible moderating effect, and evaluate its impact on individuals’ worry severity and symptoms of GAD. The first of these studies (N = 573) investigated the moderating effect of metacognitions on the relationships anxiety sensitivity has with worry severity and GAD in an undergraduate sample. The second of these studies (N = 627) expanded upon the first. It investigated the indirect pathways from neuroticism to worry severity and GAD, through anxiety sensitivity and intolerance of uncertainty. Its primary focus was to then investigate if these indirect pathways would be moderated by metacognitive beliefs. Overall, these studies did not conclude that metacognitions play a moderating role in the relationships neuroticism, anxiety sensitivity, and intolerance of uncertainty have with worry severity and GAD. Despite this, it was still found that anxiety sensitivity and intolerance of uncertainty were significant mediators in the indirect pathways that connect neuroticism to worry severity and GAD. This would suggest that future research may wish to further investigate these mediational pathways, and possibly incorporate metacognitions as mediating rather than moderating variables.
Keywords: Generalized Anxiety Disorder (GAD); metacognitions